Case Report: Endoscopic cystectomy vs. lumbar interbody fusion for liquid- and gas-filled discal cysts: a case series and literature review - Huang, Haoyun; Li, Guangye; Deng, Junwen; Chen, Rigao; Zhou, Yi (Frontiers in Surgery, 2025)
Lumbar discal cysts are uncommon lesions that mimic disc herniation but require distinct therapeutic strategies because of their unique pathophysiologies. However, the current literature lacks consensus on the adoption of optimal surgical approaches. This study reviews the surgical management and pathological mechanisms of primary lumbar discal cysts, emphasizing the distinction between liquid- and gas-filled subtypes that require tailored therapeutic strategies due to their differing pathophysiologies and association with spinal instability. We report successful surgical outcomes in three patients: one with a liquid cyst treated with endoscopic resection and two with gas-filled cysts managed with endoscopic cystectomy or lumbar interbody fusion, respectively. All patients experienced significant symptomatic relief and complete cyst resolution on imaging. A concurrent PubMed literature review (1990–2025) on primary gas-filled and liquid disc cysts informed the analysis. Liquid cysts predominantly occur in young patients, and these are associated with annular fiber damage and disc herniation, causing symptoms primarily through direct compression; endoscopic cystectomy is an effective treatment. Conversely, gas-filled cysts are more common in old patients, and these are strongly linked to disc degeneration and the vacuum phenomenon. Symptoms arise not only from cyst compression but also potentially from concurrent spinal stenosis and vertebral instability. Therefore, the surgical strategy for gas-filled cysts must consider the factor of spinal stability: endoscopic cystectomy is suitable for stable spines, while interbody fusion surgery is more appropriate when instability is present. We conclude that surgical intervention is effective for disc cysts, but the optimal approach must be individualized on the basis of cyst subtype and the presence of spinal instability, as informed by clinical presentation and imaging features.